Respuesta :

we know that
in the right triangle BDC
cos C=(b-x)/a---> a*cos C=b-x-----> x=b-a*cos C
sin C=h/a-----> h=a*sin C

therefore

the answer is 
A.) x = b-acosC

Answer:

The correct option is:

A. x = b-acosC

Step-by-step explanation:

We are given a triangle ABC

in each and every option cosC is present, so we calculate the value of cosc

cosC=[tex]\dfrac{Base}{Hypotenuse}\\ \\=\dfrac{DC}{BC}\\ \\=\dfrac{b-x}{a}[/tex]

⇒  acosC=b-x

⇒  x=b-acosC

Hence, correct option is:

A. x = b-acosC

ACCESS MORE